Unveiling the hidden - anticipating the future: divinatory practices among Jews between Qumran and the modern period - Rodríguez-Arribas, Josefina; Greenbaum, Dorian Gieseler (Prognostication in History, 2021)
Acknowledgments -- List of Figures and Tables -- Table for the Transliteration of the Hebrew Characters -- Table for the Transliteration of the Arabic Characters -- Notes on the Contributors -- Introductory Essay: Divination in Jewish Cultures-Some Reflections on the Subject of This Book -- Josefina Rodríguez-Arribas -- 1 Divination as Transaction: Rhetorical and Social Dimensions of Ancient Jewish Divination Texts -- Michael D. Swartz -- 2 Aramaic Calendars and the Question of Divination in Late Second Temple Judaism -- Helen R. Jacobus -- 3 Jewish Oneiric Divination: From Daniel's Prayer to the Genizah Šeʾelat Ḥalom -- Alessia Bellusci -- 4 Dream Interpretation Reinterpreted in the Light of Judaeo-Arabic Fragments Attributed to Ḥai Gaon -- Blanca Villuendas Sabaté -- 5 If You Seek to Take Advice from the Torah, It Will Be Given -Jewish Bibliomancy through the Generations -- Shraga Bar-On -- 6 Judah bar Barzillai and His Role in Abraham bar Ḥiyya's Letter on Astrology -- Josefina Rodríguez-Arribas -- 7 Abraham bar Ḥiyya's Letter to Judah bar Barzillai-Translation -- Josefina Rodríguez-Arribas and Amos Geula -- 8 Maimonides on Magic, Astral Magic and Experimental Science -- Dov Schwartz -- 9 On the Various Faces of Hebrew Physiognomy as a Prognostic Art in the Middle Ages -- Joseph Ziegler -- 10 Inscriptio characterum : Solomonic Magic and Palaeography. With an Appendix on the Making of the Grimoire by Nicholas Pickwoad -- Charles Burnett -- Bibliography -- Index of Names (People, Places, and Texts) -- Index of Quotations and Citations of Biblical, Pseudepigrapha, Qumran, and Rabbinic Texts -- Index of Subjects.